Recent developments in purification techniques and industrial applications for whey valorization: A review. Issue 1 (2nd January 2020) - Kaur, Navpreet; Sharma, Poorva; Jaimni, Seema; Kehinde, Bababode Adesegun; Kaur, Shubhneet
Abstract: Whey is considered as a by-product of dairy industries and commonly regarded as waste. Despite being a good source of nutrients (lactose, minerals, and bioactive peptides), it is commonly discarded as effluent. Innovative techniques such as membrane filtration, chromatography (affinity and ion exchange), chemical treatments, and/or combination of these are used for the extraction of these constituents. The presence of these components in whey makes it functional in food and pharmaceutical industries. This article is aimed at supplementing recent information to available literature about different novel techniques used for the separation of whey constituents and their industrial application. In future, information reviewed will be helpful for the processors to select the best technique for the separation of individual constituents for the attainment of maximum yield and purity.